Using word-picture verification to inform language impairment locus in chronic post-stroke aphasia - Durfee, Alexandra Z.; Harnish, Stacy M. (Frontiers in Rehabilitation Sciences, 2022)
Word-picture verification, a task that requires a yes/no response to whether a word and a picture match, has been used for both receptive and expressive language; however, there is limited systematic investigation on the linguistic subprocesses targeted by the task. Verification may help to identify linguistic strengths and weaknesses to ultimately provide more targeted, individualized lexical retrieval intervention. The current study assessed the association of semantic and phonological skills with verification performance to demonstrate early efficacy of the paradigm as an aphasia assessment. Sixteen adults with chronic post-stroke aphasia completed a battery of language assessments in addition to reading and auditory verification tasks. Verification scores were positively correlated with auditory and reading comprehension. Accuracy of semantic and phonological verification were positively correlated with accuracy on respective receptive language tasks. More semantic errors were made during verification than naming. The relationship of phonological errors between naming and verification varied by modality (reading or listening). Semantic and phonological performance significantly predicted verification response accuracy and latency. In sum, we propose that verification tasks are particularly useful because they inform semantics pre-lemma selection and phonological decoding, helping to localize individual linguistic strengths and weaknesses, especially in the presence of significant motor speech impairment that can obscure expressive language abilities.